STRUCTURAL DESIGN OF AL JABBAR GREAT MOSQUE - Gunawan, Richard
This Final Project discusses about the structural design of Great Mosque of Al Jabbar which is located in Bandung. In general, the structural design consists of reinforced concrete structure and steel roof structure. In addition, because the location of the building is an area with a relatively high earthquake risk, the building will be designed as an earthquake resistant building that referring to SNI 1726:2019. And the value of loading on the building will refer to SNI 1727:2018. The reinforced concrete structure has 1 floor with a height of 6 metres and a mezzanine floor with a height of 4 metres. The span between the building columns is 9,9 metres. In general, the ground floor functions as a musem and the 1st floor and mezzanine floor functions as a praying room. In designing this reinforced concrete structure, it referring to SNI 2847:2019. The steel roof structure is a space frame structure in the form of a pyramidal curve with a span of 99 metres and a height of 52 metres. Considering the size of the roof and the width of the roof span, it is necessary to design a temporary structure during the roof construction to avoid construction failure. In designing this steel roof structure, it referring to SNI 1729:2020 and ASCE 37-14 for the temporary structure. In the final product of this design, there will be various kinds of the dimensions and detailed components of each structural element that compose the Al Jabbar Grand Mosque building and the temporary structural designs needed during the roof construction.